ANALYSIS OF FAIR USE PRINCIPLES OF RELIGIOUS LECTURES DISSEMINATED BASED ON COPYRIGHT LAW - Wendelyn Winona Widyadari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of technology, particularly social media, has created new opportunities for the dissemination of religious lectures while also raising challenges related to copyright infringement. Religious lectures are categorized as works protected under Law Number 28 of 2014 on Copyright through both moral and economic rights, although this protection intersects with the principle of fair use, which allows the use of works under certain conditions such as for education or public interest. This study aims to analyze the application of fair use to religious lectures distributed via social media and to examine how the exclusive rights of creators can be safeguarded without neglecting public access. The findings indicate that lectures merely quoting scriptures are not considered original works, while those that include interpretation and creativity by the speaker remain protected by copyright. The dissemination of lectures without permission, especially for commercial purposes, constitutes a copyright infringement. Therefore, a balance between the moral and economic rights of creators and the public's interest in accessing religious information is necessary to create a fair, ethical digital